Pengawasan Atas Penyelenggaraan Pemerintahan Daerah Untuk Mewujudkan Pemerintahan Daerah yang Efektif dan Efisien - Amalia Diamantina (Faculty of Law, Universitas Diponegoro, 2010)
As consequences of decentralization principle enforcement as framework of developing relationship between central government and regional government its needed a comprehensive understanding in the relationship pattern between central government and regional government. The freedom and selft assessment regional affair in the frameork of NKRI, because regional is given arbitrary in handling local affair which is given by central government. In related with he mention above, monitoring and controlling the administration of regional government should be placed as media of coornation between contral government and regional government in order to in creasing effectiveness and efficeinlty of carry on of governmental administration